Direito ao trabalho no sistema capitalista brasileiro e o contrato de trabalho intermitente - Krusche, Paulo Cezar (2020)
The research deals with the Right to Work as a basic right of social rights, as it is through work that human beings obtain social recognition and the only probable way to acquire goods, starting with survival. Therefore, since work is a social right, the generation of formal work must be decent. However, going against the generation of decent formal work, the modality of intermittent work contract, inserted in the national system, through the Labor Reform of 2017 is presented. In this modality, the worker will receive only for the period that is called to provide the service, if there is no call, will not receive a salary. Furthermore, this puts the worker in a condition of high instability, uncertainty and insecurity about his own social reproduction. The objective of the research is to demonstrate that the Right to Work should not be considered a right to have only one job, but to have a job in decent conditions, which is not seen with the intermittent contract mode, since, in this type of work, the worker lives a permanent anguish due to the uncertainty of the call, and the employer may use the summons to exploit this employee more and more. This type of contract aims at reducing rights, seeking exclusively to increase corporate profitability and to reduce business risks. In his study, Karl Marx pointed out that in the capitalist world there is the domination of one class (capitalists) over the other (proletarians), with a view to the exploitation of labor and the tendency to expand, supposedly without limits of capital, culminating in the exclusion of a great part of the population, workers. Associated with these questions to the theme Right to Work as the right to decent work, the Federal Constitution of 1988 in its article 1, item IV, provides the social values of work and free enterprise, whereas article 6 refers to work as a fundamental social right, article 170 refers to work as being the foundation of the economic order. Still, in the same article 170, in item VIII, there is an allusion to the search for full employment as one of the guiding principles. Thus, it appears that the intermittent contract model makes work more flexible and precarious, going against what the Federal Constitution provides. This type of contract must be largely modified and regulated in order to guarantee the minimum social rights provided for. The research is justified by the relevance and importance of the topic, since work is a vital activity for human beings and should not be made precarious to the point of leaving the worker in the uncertainty of when he will receive his salary. The bibliographic review used the doctrine, legislation and geographic statistics, linking to the bases of Marxist historical materialism, through the historical-deductive method, through the monographic procedure. The procedures and techniques employed were files, abstracts and extended abstracts. The first chapter deals with the right to work in Brazil and in the world, as well as work that creates values, making work more flexible and precarious. The second chapter deals with Labor Reform, the employment and employment relationship, the employment contract and the type of intermittent employment contract, as well as the comparative law and statistical data on hiring workers in this modality. It appears that the great challenge is to ensure the formal incorporation of the concept of decent work into Brazilian law, its effectiveness in the face of the damaging effects of the intermittent employment contract imposed on Brazilian workers. Decent work refers to the aspirations of human beings in the professional domain, covering opportunities to perform productive work with equitable remuneration; workplace safety and social protection for families; better prospects for personal development and social integration; freedom to express their concerns; organization and participation in decisions that affect their lives; and equal opportunities and treatment for all men and women.